APPLICATION OF THE DISCOVERY LEARNING MODEL TO IMPROVE CRITICAL THINKING ABILITY IN VIBRATION AND WAVE MATERIALS - Boi, Oliviana Monik; Ain, Nurul; Jufriadi, Akhmad (Journal of Teaching and Learning Physics, 2022)
The aims of this study are (1) to determine the quality of the application of discovery learning learning models in improving students' critical thinking skills on vibration and waves, (2) whether the application of discovery learning models can improve students' critical thinking skills on vibrations and waves. This type of research is Classroom Action Research with a research design using the Lewin model. The subjects of this study were students of class VIII.2 SMP Nahdlatul Ulama, totaling 30 students. Data on the implementation of learning was obtained from the observation sheet on the implementation of learning, while the data on critical thinking skills was obtained from a multiple-choice test with reasoned. The results showed that, (1) The application of the discovery learning learning model can improve students' critical thinking skills in students' science learning, this can be seen from the results of the observation analysis of the implementation of the discovery learning learning model cycle I and cycle II which experienced a good increase of 18, 07%, that is from 62.93% to 81%. (2) There is an increase in critical thinking skills by applying the discovery learning learning model in terms of aspects, namely critical thinking indicators, namely the first cycle of 65% and the second cycle of 77% with an increase of 12%. Based on the results of the study, it can be concluded that by applying the discovery learning model, it can improve students' critical thinking skills in science learning with good improvement.